Effect of high-flux and low-flux hemodialysis on survival rate of maintenance hemodialysis patients:A Meta analysis - DU Li-guo; XU Xiao; HU Yu-gang; LI Xiao-ning (Linchuang shenzangbing zazhi)
Objective To compare the impact of high-flux hemodialysis(HFHD) and low-flux hemodialysis(LFHD) on survival rate of maintenance hemodialysis(MHD) patients.Methods We searched Cochrane Library,PubMed,Embase,CNKI,Wanfang data and VIP from the establishment of the database to March 1,2016 to identify random controlled trials(RCT) and prospective controlled trials(PCT) on the impact of HFHD and LFHD on survival rate of MHD patients.The quality of the selected trials was appraised and the data were extracted according to the inclusion and exclusion criteria.RevMan 5.2 software was used for the Meta analysis.Results Eight researches involving 8 561 patients were included in this study.The Meta analysis found that in MHD patients,HFHD patients had higher long-term survival rate than LFHD patients[HR= 0.71,95%CI:(0.63,0.8),P<0.05].In further subgroup analysis,it was found that HFHD patients had lower all-cause mortality(ACM)(P<0.05) no matter the follow-up period was longer than 3 years or not In MHD patients,the cardiovascular mortality was higher than the incidence of death caused by infection(P<0.05).As compared with the LFHD patients,HFHD patients had lower cardiovascular mortality[OR = 0.79,95%CI:(0.65,0.96),P = 0.02],No difference was found in infection-associated mortality between HFHD and LFHD patients[OR= 0.90,95%CI,(0.69,1.18),P = 0.45].Conclusions Based on this Meta analysis,HFHD can improve the long-term survival rate in MHD patients and reduce cardiovascular mortality.